2009
DOI: 10.1002/jcb.22209
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fat and muscle mass associated with a functional human polymorphism in a post‐transcriptional BMP2 gene regulatory element

Abstract: A classic morphogen, bone morphogenetic protein 2 (BMP2) regulates the differentiation of pluripotent mesenchymal cells. High BMP2 levels promote osteogenesis or chondrogenesis and low levels promote adipogenesis. BMP2 inhibits myogenesis. Thus, BMP2 synthesis is tightly controlled. Several hundred nucleotides within the 3′ untranslated regions of BMP2 genes are conserved from mammals to fishes indicating that the region is under stringent selective pressure. Our analyses indicate that this region controls BMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 54 publications
1
47
0
1
Order By: Relevance
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies with healthy human subjects, e.g., several genetic variations (Riechman et al 2004;Devaney et al 2009;Walsh et al 2012;Van Deveire et al 2012), differences in skeletal muscle gene Raue et al 2012;Phillips et al 2013) and microRNA expression (Davidsen et al 2011), phosphorylation status of signaling proteins (Mayhew et al 2011;Mitchell et al 2013), androgen receptor concentrations (Ahtiainen et al 2011;Mitchell et al 2013), and satellite cell count (Petrella et al 2008) have been suggested to segregate high and low responders to RTinduced muscle hypertrophy. The physiological aspects of individual variation in phenotype responses to RT are apparently very complex phenomena and more studies specifically focused on high and low responders are required to reveal unambiguously the mechanisms of individual differences in RT-induced adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has linked aberrantly elevated and prolonged expression of ARE-encoding mRNAs to cancer, including those participating in angiogenesis, chemotaxis, and invasion. Examples of such genes include EGF, estrogen receptor (ER), COX-2, VEGF, matrix metalloproteinase (MMP) 1, the chemokine receptor CXCR4, and urokinase-type plasminogen activator (uPA) and its receptor (4)(5)(6)(7)(8)(9). The ARE-mRNAs are regulated by trans-acting RNA-binding proteins notably tristetraprolin (TTP/ZFP36) and human antigen R (HuR/ELAVL1).…”
Section: Introductionmentioning
confidence: 99%
“…Repressors can block every intracellular signaling transduction step [32; 33]. Negative post-transcriptional regulatory mechanisms also may influence BMP2 expression [34; 35]. A growing body of evidence indicates that relief of repression at multiple regulatory levels is an important means of controlling BMP2 gene expression.…”
Section: Introductionmentioning
confidence: 99%